Pengaruh Persepsi Harga, Social Media Marketing dan Citra Merek terhadap Keputusan Menginap di Hotel Le Meriden Jakarta - Azhar; Ricky Talumantak (LPPM Universitas Asa Indonesia, 2025)
The purpose of this study is to find the effect of of price perception, social media marketing, and brand image on the decision to stay at Le Meridien Hotel Jakarta. This research employs an accidental sampling technique, where respondents were selected based on individuals who happened to be at the lodging location and were willing to provide information regarding their decision in choosing a place to stay. In line with the descriptive quantitative approach used in this study, a survey method was employed by distributing questionnaires to consumers. The survey was conducted using structured questionnaires to collect data and to analyze the relationships among the hypotheses in this research model using multiple linear regression analysis. The sample consisted of 100 hotel guests who were planning to stay. Based on the t-test, it was found that brand image does not have a significant effect on the decision to stay, while the variables of price perception and social media marketing each have a positive and significant partial effect on the decision to stay. The F-test results show that price perception, social media marketing, and brand image simultaneously have a significant effect on the decision to stay